Analysis of Illocutionary Acts in Instagram Captions about Covid-19 - Harto Malik; Rahman Taufiqrianto Dako; Rosdiana Abdullah (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The Covid-19 pandemic has altered communication patterns, particularly on social media, where Instagram has become the main platform for disseminating information, opinions, and emotions related to this global crisis. This study aims to explore the types of illocutionary speech acts in the Instagram captions of the WHO account related to Covid-19. This research is a descriptive qualitative study. The data in this research consists of captions and sentences containing illocutionary speech acts, while the data source is the Instagram captions from the WHO's Instagram account about Covid-19 during the pandemic. The method used in this research is the non-participant observation method. The researcher observed the captions on WHO’s Instagram about Covid-19 during the pandemic by recording and noting them. Additionally, the researcher transcribed the caption data into written form. After collecting the data, the researcher performed reduction, classification, verification, and tabulation based on their types. Next, the researcher coded the data, interpreted it, and drew conclusions. The results of this study identify five types of illocutionary speech acts in WHO’s Instagram captions about Covid-19, namely representative, directive, expressive, commissive, declarative, declarative & directive, and directive, representative, & declarative. The findings from this research could significantly influence communication strategies and policies by offering a deeper understanding of how illocutionary speech acts are utilized in health-related messaging. By analyzing the WHO's Instagram captions about Covid-19, this study reveals how specific language choices can effectively convey critical information, persuade audiences, and encourage public compliance with health guidelines. These insights can be applied to refine future health communication campaigns, ensuring that messages are not only clear and informative but also strategically crafted to achieve desired behavioral outcomes on a global scale.